Temporal PROMETHEE II — New multi-criteria approach to sustainable management of alternative fuels consumption - Wątróbski, Jarosław (Journal of cleaner production, 2023)
Alternative fuels are the subject of growing interest among both researchers and practitioners. In this aspect, to properly handle the problem of proper evaluating alternative fuels, appropriate methods, and tools are undoubtedly needed. Since the evaluation of sustainable alternative fuels similarly, like most sustainability problems, has a multi-criteria character, multi-criteria methods have the potential to be employed here. Analysis of the alternative fuels domain indicates that classical multi-criteria methods are not exactly suitable for use in cases where, instead of a single matrix for evaluating alternatives, we have a set of them collected for particular periods. Therefore, developing a dedicated approach that considers the specifics of a given problem is necessary. For this purpose, the paper proposes a new Temporal Preference Ranking Organization Method for Enrichment Evaluations II (PROMETHEE II) method for multi-criteria temporal evaluation. Hence, the presented method solves the limitations occurring in previously developed multi-criteria methods. In addition to the classical aspect of evaluating the options under consideration, the proposed method makes it possible to accurately grasp the dynamics of the outcomes and put them into an easy-to-interpret result. A practical contribution of the paper is applying the developed method to a multi-criteria temporal evaluation of sustainable consumption of alternative fuels in road transport. For this purpose, an assessment model was built based on the data for 32 European countries acquired from the European Union’s statistical office (Eurostat). Preference imprecision modeling and model sensitivity analysis demonstrated the analytical potential of the developed sustainability assessment model and, simultaneously, the Temporal PROMETHEE method’s superiority. The comparative analysis of the Temporal PROMETHEE II method clearly shows that the results are robust and reliable, and the developed method is suitable for evaluating various temporal sustainability problems. The research demonstrated that a model alternative fuel mix and its shape as well as progression is maintained by Scandinavian countries such as Norway and Sweden. [Display omitted] •A new temporal method for multi-criteria sustainability assessment.•Public available algorithm and code of method developed.•An evaluation of sustainable consumption of alternative fuels.